SOME ASPECTS OF THE COURSE OF ACUTE GLOMERULONEPHRITIS WITH NEPHROTIC SYNDROME IN CHILDREN - Ibatova Sh.M., Islamova D.S., Ibragimova Yu.B. (Zeta Repository, 2023)
In the development of chronic renal failure in children, the proportion of glomerulonephritis is still significant. Identification of chronic kidney pathology at the initial stage is important to improve the effectiveness of preventive and therapeutic measures aimed at slowing down the progression of the disease. We examined 76 patients with acute glomerulonephritis with nephrotic syndrome aged 2 to 5 years, including 31 boys and 45 girls. The development of the forecast algorithm was carried out by the method of sequential Wald analysis. A score of 10 was used as a threshold to conclude on the prognosis. The peculiarity of the course of glomerulonephritis in children was that the disease develops against the background of hereditary predisposition.